Essays on micro and small firms in Indonesia - Lau, Siew Yee (2020)
I write three essays on micro and small firms in Indonesia. The first essay discusses the effects of the education of entrepreneurs—the managers cum owners of micro and small firms—on the firm performance and the entrepreneurs’ earnings. I find some evidence that, on average, better educated entrepreneurs earn more hourly, monthly, and annually, though the return to education differs by sector. I also find female entrepreneurs benefit more from their education, so do entrepreneurs in urban areas. The second essay studies whether social health insurance in Indonesia, Askeskin, that owners of micro and small firms have access to help the firms cope with family hardships experienced by the households. I find some evidence of Askeskin reduces the adverse effects of deaths in the family in the previous year, outpatient care, and traffic accidents on net profits; Askeskin also protects total assets against owners’ need of outpatient care. The third essay analyses the effects of an increase in real wage rates on small farms’ investment in tractors, machines, equipment, and irrigation system, i.e., whether an increase in wages induces farmers to substitute labour for capital. I find some evidence that higher real minimum wages induce greater use of tractors on small farms; higher real agricultural wages encourage smallholders invest more in vehicles. I also find relatively large farms use more tractors as real wages (all types) increase; they also invest more in vehicles when farm labour become more expensive. By contrast, relatively small farms invest more in irrigation systems in response to higher real wages and more in farm equipment when real agricultural wages increase.